Narratives of type 2 diabetes mellitus patients regarding the influence of social issues on diabetes self‐management: Implications for patient care - Kwadwo Ameyaw Korsah; Joana Agyeman‐Yeboah (Nursing Open, 2023)
Abstract Aim To explore the perspectives of individuals living with type 2 diabetes mellitus on the influence of social factors on diabetes self‐management in Ghanaian context. Design Hermeneutic phenomenological approach to qualitative research was used. Method A semi‐structured interview guide was used to collect data from 27 participants who were newly diagnosed with type 2 diabetes. Analysis of data was carried out by using content analysis approach. One main theme with five subthemes emerged. Results Participants experienced social stigma due to the changes in their physical appearance. Mandatory isolation was created by participants in order to manage the diabetes. The financial status of the participants was affected by the diabetes self‐management. Differing from the social issues, the overall participants' responses to experiences living with type 2 diabetes mellitus culminated with psychological or emotional hassles, and therefore, patients resorting to alcohol consumption to deal with diabetes related stress, fears, anxiety, apprehension and pain among others.